Preparing Leadership in Developed Countries (Spandan, 2018)
Today, most scientists and researchers of education believe that if it is supposed to have a change in education field today, it should be started from education management (Behbahani, 2011). The subject of this research is the necessity of training educational managers and leaders. School leaders are the most important agent for educational institutions. School’s overall performance depends on the leader of the school. They are in charge with guiding and supervising teachers during education activities. School managers are extremely important for carrying out schools’ vision and mission. In this case, splendidly training school managers who have such an importance for education systems and bring them in equipment which is required for serving their school well enough have quite importance (Tugba Turabik,Gulsun, Atanurbaskan, Seval Kocak, 2014). Various countries of the World have practiced for school leader development training. In this study, certain developed countries’ schools leaders’ development models are studied.